2014
DOI: 10.1371/journal.pone.0105248
|View full text |Cite
|
Sign up to set email alerts
|

Surface Survival and Internalization of Salmonella through Natural Cracks on Developing Cantaloupe Fruits, Alone or in the Presence of the Melon Wilt Pathogen Erwinia tracheiphila

Abstract: Outbreaks of foodborne illness attributed to the consumption of Salmonella-tainted cantaloupe have occurred repeatedly, but understanding of the ecology of Salmonella on cantaloupe fruit surfaces is limited. We investigated the interactions between Salmonella enterica Poona, the plant pathogenic bacterium Erwinia tracheiphila, and cantaloupe fruit. Fruit surfaces were inoculated at the natural cracking stage by spreading S. enterica and E. tracheiphila, 20 µl at 107 cfu/ml, independently or together, over a 2×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Similarly, 6 log CFU of S. typhimurium was recovered from mango skin sections following an inoculum contact time of 24 h ( Fernandes et al, 2014 ). Beyond attachment, using SEM, Gautam et al (2014) demonstrated the presence and survival of Salmonella Poona on cantaloupe rinds until 24 days post-inoculation. Survival of pathogens on fresh produce, particularly in the post-harvest environment is primarily influenced by ambient fruit handling/storage conditions (temperature and relative humidity) and packing house practices such as waxing ( Guo et al, 2002 ; Kenney and Beuchat, 2002 ; Shi et al, 2007 ; Collignon and Korsten, 2010 ; Huff et al, 2012 ; Tian et al, 2013 ; Zhou et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, 6 log CFU of S. typhimurium was recovered from mango skin sections following an inoculum contact time of 24 h ( Fernandes et al, 2014 ). Beyond attachment, using SEM, Gautam et al (2014) demonstrated the presence and survival of Salmonella Poona on cantaloupe rinds until 24 days post-inoculation. Survival of pathogens on fresh produce, particularly in the post-harvest environment is primarily influenced by ambient fruit handling/storage conditions (temperature and relative humidity) and packing house practices such as waxing ( Guo et al, 2002 ; Kenney and Beuchat, 2002 ; Shi et al, 2007 ; Collignon and Korsten, 2010 ; Huff et al, 2012 ; Tian et al, 2013 ; Zhou et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, mangoes can get contaminated within the pre and post-harvest environments ( Fatica and Schneider, 2011 ; Penteado, 2017 ). In the orchards, mango trees are cultivated and fruit are harvested in their natural environment where they are exposed to a variety of contamination sources including soil, irrigation water, manure, and animals in or near the field ( Fatica and Schneider, 2011 ; Huff et al, 2012 ; Gautam et al, 2014 ). This of particular significance with pathogens such as Salmonella since they normally reside in the intestinal tract of animals and can therefore gain entry into the pre-harvest environment through contaminated animal feces ( Fatica and Schneider, 2011 ; Tomas-Callejas et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous ClO 2 (3 ppm) reduced the L. monocytogenes population by 3.7 log CFU when bell pepper surfaces were not injured and by 0.44 when injured [38]. Reduced efficacy of the treatments in our study may be due to a higher level of bruises and attached soiled particles which may have allowed bacterial cells to hide better in the surfaces limiting the access to the sanitizer solutions [43,44]. However, a further rigorous study is needed to better understand the influence of individual factors on the efficacy of the sanitizer.…”
Section: Effects Of Aqueous Clo 2 On E Coli O157: H7 and Salmonella mentioning
confidence: 71%
“…Bacterial cells embedded within the crevices and fissures of the watermelon rind may be another factor. Cracks and fissures on melon rind surfaces may allow bacterial cells to enter interior tissues [64]; this phenomenon may limit the access of bacterial cells to the applied sanitizer solutions. E .…”
Section: Discussionmentioning
confidence: 99%